Comparação do nível de informação entre cirurgiões dentistas e universitários sobre lesões dentárias não cariosas - Cassita, Flávia Regina de Oliveira (2019)
The term non-carious dental lesion (LDNC) is a type of dental lesion that is found quite frequently in the dental clinic and described as a complex and multifactorial phenomenon, exacerbated with the advancement of age and is defined as an irreversible loss of the mineralized tissue of the dental structure, with factors often misunderstood. The diagnosis requires attention in its clinical aspects, in the anamnesis, considering the clinical history, alimentary habit, oral hygiene, para-functional habits, presence of systemic diseases and use of medications. The terms erosion, abrasion, abfraction, and attrition are the accepted terminologies, however, it is notorious that these terminologies are used interchangeably, leaving the Dentist (CD) unsafe to diagnose, treat, and prevent the appearance of new lesions. The objective of this study was to know and to compare the level of information of the Dentist with the students of the Dentistry course of Universidade do Sagrado Coração (USC), about LDNC. In this way, a questionnaire regarding the LDNC was delivered to the CDs and students. The results were described by absolute and relative frequency. The Chi-square test was used to associate the responses between the two groups (p <0.05). The question of nomenclature did not reach 100% of correct answers, with erosion predominating in both groups. In the question about knowledge of etiological factors, none of the groups reached 100% of the responses, predominating erosion and abrasion factors, and for reflux, there was a statistical difference. Regarding how to identify an LDNC, both groups related to the presence of cervical wear and, about 50% related to incisal/palatal and ice pain, but few mentioned hot pain and gingival recession. For both groups, the removal of the etiological factors will reduce the appearance of new lesions. An open question about why LDNC are treated, most CDs and students answered that it should be treated to improve the quality of life of patients. In order to monitoring the LDNC, to avoiding the appearance of new lesions or to controlling the existing ones, the groups responded with a greater percentage (60% and 70%) to the alternative "brushing instruction". About dentin hypersensitivity, 100% answered that knew what HD is. For the treatment of HD, the desensitizing option was the most outstanding. The greatest divergences in the groups were observed in relation to treatment with fluoride, application of varnish, laser therapy and endodontic treatment. About the systemic conditions, 100% of the CDs and students knew of the relationship and most answered that stress, reflux, bulimia, bruxism and malocclusion are related to LDNC. In the issue that addressed quality of life, 100% of CDs and 87% of students said that LDNC influences the quality of life of people. It was concluded that CDs and students present similar knowledge. However, they did not obtain 100% correct answers in almost all the alternatives, showing some deficiency or conflict on the subject and treatment of the lesions.